Population characteristics of pallid sturgeon, Scaphirhynchus albus (Forbes & Richardson, 1905), in the lower Platte River, Nebraska. (22nd August 2014) - Hamel, M. J.; Pegg, M. A.; Hammen, J. J.; Rugg, M. L.
Summary Pallid sturgeon, Scaphirhynchus albus (Forbes & Richardson, 1905), have been studied intensively in recent years to understand a declining adult population that does not seem to be naturally reproducing; however, most of this effort has occurred in the main‐stem Missouri and lower Mississippi rivers. Pallid sturgeon are known to occupy tributary streams intermittently, but the importance of tributaries for completion of essential life stages for pallid sturgeon remains unknown. Tributaries may provide uses for fish spawning and reproduction, nursery or refuge habitat, and areas for foraging. Therefore pallid sturgeon population characteristics were studied in the Platte River, Nebraska, a large tributary to the Missouri River. During 2009–2012 137 pallid sturgeon were captured. Pallid sturgeon were found throughout the lower 159 km of the Platte River throughout the entire year (March–November); however, pallid sturgeon were more abundant in the lower‐most 52 km during 2009 and 2010. Capture locations were in comparatively deeper water along flow gradients between the thalweg and mid‐channel sandbars. Most pallid sturgeon were of hatchery origin and dispersed an average of 197.5 km (±233 SD) from the original stocking location to the Platte River capture site. Although the direct reasons for are unknown, the lower Platte River may be providing habitat or resources that are not typically found in the channelized Missouri River. Continued research in the Platte River and other large tributaries may provide insight for recovery of endemic, large‐river species. Persistence of large‐river fishes may depend on population connectivity at multiple scales; identifying these connections is critical.